1996
DOI: 10.1111/j.1432-1033.1996.00328.x
|View full text |Cite
|
Sign up to set email alerts
|

Phytanic Acid is a Retinoid X Receptor Ligand

Abstract: Metabolic defects in phytanic acid catabolism have been shown to be connected with a number of human diseases which can lead to lethal defects of the nervous system and other organs. These effects are probably a result of the very high accumulation of phytanic acid in tissues throughout the body, due to defects in phytanic acid oxidation, the peroxisome being a major site for this process. The nuclear hormone receptors peroxisome proliferator-activated receptor and retinoid X receptor (RXR) have been shown to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
98
0
3

Year Published

1999
1999
2016
2016

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 148 publications
(105 citation statements)
references
References 24 publications
4
98
0
3
Order By: Relevance
“…Several molecules have been described as potential endogenous ligands for RXR ( Figure 3): 9-cis RA, 16 phytanic acid 69 and docosahexaenoic acid, 70 but none of these has been proved to be the bona fide endogenous ligand so far. Perlmann and co-workers created a ligand detector mouse line.…”
Section: Ligandsmentioning
confidence: 99%
“…Several molecules have been described as potential endogenous ligands for RXR ( Figure 3): 9-cis RA, 16 phytanic acid 69 and docosahexaenoic acid, 70 but none of these has been proved to be the bona fide endogenous ligand so far. Perlmann and co-workers created a ligand detector mouse line.…”
Section: Ligandsmentioning
confidence: 99%
“…DHA is an essential nutrient for adequate retina and brain development (de Urquiza et al, 2000;Uauy et al, 2001). Both phytanic acid ( (Kitareewan et al, 1996;Lemotte et al, 1996;Radominska-Pandya and Chen, 2002) and DHA are the RXR natural ligands (de Urquiza et al, 2000;Uauy et al, 2001). In this project, we have observed that phytanic acid and DHA, alone and with RAR agonists, suppressed the growth of human prostate cancer cells and decreased the protein level of cyclin D1, a cell cycle regulator.…”
Section: Introductionmentioning
confidence: 65%
“…Two other RARinteracting retinoids have been identified in tissue: all-trans 13,14-dihydroretinoic acid and beta -apoands-14'-carotenal [32,33]. Phytanic acid [34], docosahexaenoic acid [35] and other unsaturated fatty acids [36] have been proposed as additional/alternative ligands for RXRs. Future research may investigate the binding abilities FARs to leukotrienes and prostaglandins, both of which are compounds involved in the inflammatory response [18].…”
Section: Future Directions and Parasitic Fars As Targets In Drug Devementioning
confidence: 99%